PENGARUH KEPERCAYAAN NASABAH TERHADAP TABUNGAN HAJI DI BANK SYARIAH INDONESIA - Mufid, Fatiyah; Agestia Dewi Rahajeng; Aziizah Nur Pratiwi; Andi Amri (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2023)
Bank Syariah Indonesia is the largest sharia banking in Indonesia due to the merger of three state-owned banks. One of the savings products is Hajj Savings. This Hajj savings can be used for planning Hajj or Umrah using a mudharabah agreement. This segmentation of Hajj Savings can be used for all customers with different savings product categories. This research uses a qualitative method where data is collected from journals, books and websites. The purpose of this research is to analyze customer or public trust in Hajj Savings at BSI. So customer trust in BSI products is very important. Research shows that customer confidence in saving at Bank Syariah Indonesia is high, as seen from survey data regarding Hajj planning on the BSI website.